Reconstruction of weathering history and paleoclimatic conditions of the campano-maastrichtian sandstones in The Northern Bida Basin, Nigeria - S. A. Adepoju; O. J. Ojo; S. O. Akande; B. Sreenivas; E. V. S. S. K. Babu; T. Vijaya Kumar (Discover Geoscience)
Abstract The Campanian–Maastrichtian siliciclastic sequences in the northern Bida Basin Nigeria were studied in this research. The aim is to evaluate petrographic and geochemical (major, trace, and rare earth elements) compositions towards reconstruction of the paleoweathering history, maturity and the prevailing climatic conditions during Campano-Maastrichtian period. Petrographic results revealed that the sandstones of the Campanian Bida Formation and the Maastrichtian Enagi Formation comprises of Q93.51-100F0-2.60L/R0-3.90 and Q84.42–98.72F0-3.75L/R1.18–15.58 respectively as the framework modal composition, therefore, Bida Sandstone are classified as mostly quartzarenite with minor sublitharenite, whereas Enagi sandstone are comprises of mostly sublitharenite with minor quartzarenite. Higher chemical index of alteration (CIA), chemical index of weathering (CIW), plagioclase index of alteration (PIA), and chemical proxy for alteration (CPA) values, with the plots clustering towards and around “A” axis in the ternary (A–CN–K and A–CNK–FM) diagrams suggest that the sediments have been subjected to an intense weathering and reworking at the source. Geochemical proxies and plots revealed deposition under warm and humid paleoclimatic settings. The LREE enrichment in relation to the HREE with low negative europium (Eu/Eu*) anomaly values, as well as bivariate and ternary discrimination diagrams suggest that the Bida and Enagi sandstones were sourced from felsic rocks’ provenance within a passive margin paleotectonic settings. The regionally extensive Southwestern Basement Complex of Nigeria is suggested as the main sediments’ source for the clastic sediments within the study area.